Global News Exposure and Perinatal Anxiety in Pregnant Women: A Cross-Sectional Study - Güngör, Süleyman; Gürcan, Mehmet Buğrahan; Kanbak, Ayşe Rabia (The European Research Journal, 2026)
Objective: This study aimed to investigate the relationship between global news exposure and perinatal anxiety levels among pregnant women.Methods: This cross-sectional analytical study included 180 pregnant women. Data were collected via an online questionnaire consisting of sociodemographic characteristics, global news consumption habits, and the Perinatal Anxiety Screening Scale (PASS). Correlations were assessed using Spearman analysis, and independent predictors were evaluated with multivariate linear regression.Results: A total of 169 participants were included in the final analysis. The mean PASS score was 34.2±15.8. Significant positive correlations were found between anxiety levels and daily news checking frequency (r=0.172, P=0.025), fear of missing news (r=0.154, P=0.046), repetitive checking behavior (r=0.262, P